DAMPAK IMPLEMENTASI STANDAR AKUNTANSI DAN SISTEM PENGENDALIAN INTERN PEMERINTAH TERHADAP AKUNTABILITAS KEUANGAN PEMERINTAH - Muhammad Fadil Asri; Ratna Ayu Damayanti; Nirwana Nirwana (Jurnal Ilmiah Akuntansi Peradaban, 2023)
The purpose of this study was to examine and analyze the influence of the implementation of Government Accounting Standards (GAS) and the implementation of the Government Internal Control Systems (GICS) on government financial accountability. Data collection was carried out using a questionnaire distributed to 108 SKPD employees within the Makassar City Government. The collected data were analyzed using multiple linear regression analysis with SPSS 26 software. The result of this study indicate that GAS implementation has a significant and positive effect on government financial accountability. In addition, the implementation of GICS also has a significant and positive effect on government financial accountability. The results of this study can be useful for the government as input and consideration in determining policies, especially regarding increasing government financial accountability. Keyword: Government Financial Accountability, Government Internal Control Systems, Government Accounting Standard